Hubungan Durasi Paparan Screen Time dengan Keterlambatan Perkembangan pada Anak Usia Dini - Lely Nur Azizah; Erizza Farizan Adani; Muhammad Nuril Mukminin; Satiningsih; Widia Permita Sari; Dian Aminatul Ngiffah; Fita Permata Sari (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: The increasing use of digital technology among children has raised concerns about its impact on child development. Screen time, especially in young children, is believed to influence various aspects of development, including cognitive, physical, and social skills, potentially leading to developmental delays. Objective: This study aims to examine the relationship between screen time duration and developmental delays in early childhood. Method: A quantitative approach was used, involving 164 children aged 1-3 years. After data cleaning, 121 children were selected for further analysis. Child development was assessed using the Denver Developmental Screening Test (DDST) II, and screen time was measured through questionnaires filled out by the parents. Spearman's correlation analysis was conducted to evaluate the relationship between screen time and developmental delays. Result: The analysis showed no significant relationship between screen time duration and developmental delays (p > 0.05). These findings suggest that the amount of screen exposure, whether short or long, does not directly impact developmental delays in children. Conclusion: The study concludes that while screen time may influence a child's development in various ways, it does not have a significant direct effect on developmental delays. Other factors, such as parenting styles and the child's social environment, may have a stronger influence on developmental outcomes.